Neutron star binary orbits in their host potential: effect on early r-process enrichment. Issue 1 (13th September 2019) - Bonetti, Matteo; Perego, Albino; Dotti, Massimo; Cescutti, Gabriele
ABSTRACT: Coalescing neutron star binary (NSB) systems are primary candidates for r -process enrichment of galaxies. The recent detection of r -process elements in ultrafaint dwarf (UFD) galaxies and the abundances measured in classical dwarfs challenges the NSB merger scenario both in terms of coalescence time-scales and merger locations. In this paper, we focus on the dynamics of NSBs in the gravitational potentials of different types of host galaxies and on its impact on the subsequent galactic enrichment. We find that, for a ∼ t −1 delay time distribution, even when receiving a low kick (∼10 km s −1 ) from the second supernova explosion, in shallow dwarf galaxy potentials NSBs tend to merge with a large off-set from the host galaxy. This results in a significant geometrical dilution of the amount of produced r -process elements that fall back and pollute the host galaxy gas reservoir. The combination of dilution and small number statistics produces a large scatter in the expected r -process enrichment within a single UFD or classical dwarf galaxy. Comparison between our results and observed europium abundances reveals a tension that even a systematic choice of optimistic parameters in our models cannot release. Such a discrepancy could point to the need of additional r -process production sites that suffer less severe dilution or to a population of extremely fast merging binaries.